Deleuze and the contemporary world - Buchanan, Ian, 1969-; Parr, Adrian (Deleuze connections., 2006)
This volume joins the pragmatic philosophy of Deleuze to current affairs. The twelve new essays in this volume use a contemporary context to think through and with Deleuze. Engaging the here and now, the contributors use the Deleuzian theoretical apparatus to think about issues such as military activity in the Middle East, refugees, terrorism, information and communication, and the State. The book is aimed both at specialists of Deleuze and those who are unfamiliar with his work but who are interested in current affairs. Incorporating political theory and philosophy, culture studies, sociology, international studies, and Middle Eastern studies, the book is designed to appeal to a wide audience. Contributors include: Rosi Braidotti, Claire Colebrook, Verena Conley, Eugene Holland, John Marks, Paul Patton, Patricia Pisters, Laurence J. Silberstein, Kenneth Surin and Nicholas Thoburn. Deleuze and the Contemporary World represents: a fresh perspective on current affairs a transdisciplinary response to the contemporary world a book that puts the concepts of Deleuze to work